Community Policing: Reinventing the Wheel? - Friedmann, Robert R. (International Journal of Criminology and Sociology, 2013)
Community Policing (CP) has been a much used, overused and abused term. Many blindly adopt it, others blindly reject it. This brief article argues that a cogent policing strategy that deploys CP should start with the focus on the epidemiology of crime and the understanding of how crime is produced. There is no need to reinvent the wheel of policing strategies. Just drive it.